Apelinergic system in endothelial cells and its role in angiogenesis in myocardial ischemia - Novakova, Vera; Sandhu, Gurpreet S; Dragomir-Daescu, Dan; Klabusay, Martin (Vascular pharmacology, 2016)
Apelin is a peptide known to have a vital role in cardiovascular diseases. It has been proven to induce proliferation and tube formation in endothelial cells, stabilise contacts between endothelial cells, and mediate pericyte recruitment. Since apelin level is reduced early after myocardial infarction, a supportive therapy with apelin is being investigated for its beneficial effect on blood vessel formation. It is becoming apparent, however, that the final effect of apelin often depends on stimuli the cell receives and the cross-talk with other molecules inside the cell. Hence, understanding the apelin pathway potentially can help us to improve angiogenic therapy. This review summarises recent knowledge regarding molecules involved in apelin signalling while focusing on their roles in angiogenesis within the ischemic environment after myocardial infarction.
Keywords: signální transdukce; Signal Transduction; Humans; fyziologická neovaskularizace; Angiogenesis; intracelulární signální peptidy a proteiny; [Pyr1]-apelin-13 (PubChem CID: 25078060); lidé; Signalling pathways; zvířata; infarkt myokardu; Apelin; Endothelial cells; Neovascularization, Pathologic; Intracellular Signaling Peptides and Proteins; Endothelial Cells; Apelin-13 (PubChem CID: 71433878); Myocardial Ischemia; Myocardial Infarction; Myocardial infarction; ischemická choroba srdeční; endoteliální buňky; Apelin-12 (PubChem CID: 479167); Apelin-36 (PubChem CID: 16130451); Animals; Neovascularization, Physiologic; patologická angiogeneze